Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1103/physrevb.87.121203
|View full text |Cite
|
Sign up to set email alerts
|

Including fringe fields from a nearby ferromagnet in a percolation theory of organic magnetoresistance

Abstract: Random hyperfine fields are essential to mechanisms of low-field magnetoresistance in organic semiconductors. Recent experiments have shown that another type of random field -fringe fields due to a nearby ferromagnet -can also dramatically affect the magnetoresistance. A theoretical analysis of the effect of these fringe fields is challenging, as the fringe field magnitudes and their correlation lengths are orders of magnitude larger than that of the hyperfine couplings. We extend a recent theory of organic ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In this article we generalize our previous work 15 with organic semiconductors to describe spin relaxation in a broader range of regimes of incoherent charge transport, focusing on amorphous semiconductors such as silicon (a-Si) and germanium (a-Ge) to showcase our results. This is done by explicit calculations of spin lifetimes and coherence times using continuous-time random walk (CTRW) theory 31,32 as well as with Monte-Carlo simulations.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…In this article we generalize our previous work 15 with organic semiconductors to describe spin relaxation in a broader range of regimes of incoherent charge transport, focusing on amorphous semiconductors such as silicon (a-Si) and germanium (a-Ge) to showcase our results. This is done by explicit calculations of spin lifetimes and coherence times using continuous-time random walk (CTRW) theory 31,32 as well as with Monte-Carlo simulations.…”
Section: Introductionmentioning
confidence: 83%
“…15 Some physical intuition regarding this result can be obtained by noting that P(t) = Φ(t)/γ 2 . By recalling that Φ(t) is the probability that a hop has not taken place up to time t, we see that the polarization decays as carriers hop in agreement with what is true from low disorder case.…”
Section: Spin-orbit Spin Relaxationmentioning
confidence: 95%
See 2 more Smart Citations
“…An explanation based on mixing of spin states of a spin pair on adjacent sites prior to their reaction ("two-site model") by differently oriented magnetic fields at these sites was dismissed by the authors because of the large correlation length of the fringe fields, resulting in almost completely aligned fields at adjacent sites. On the other hand, Harmon et al recently suggested the fringefield gradients might cause additional spin mixing [13]. These gradients are on the order of a few millitesla per nanometer.…”
Section: Introductionmentioning
confidence: 99%